Implementation of multimodal computed tomography in a telestroke network: Five‐year experience. (30th September 2019) - Garcia‐Esperon, Carlos; Soderhjelm Dinkelspiel, Frode; Miteff, Ferdi; Gangadharan, Shyam; Wellings, Tom; O´Brien, Bill; Evans, James; Lillicrap, Tom; Demeestere, Jelle; Bivard, Andrew; Parsons, Mark; Levi, Chris; et al.
Abstract: Aims: Penumbral selection is best‐evidence practice for thrombectomy in the 6‐24 hour window. Moreover, it helps to identify the best responders to thrombolysis. Multimodal computed tomography (mCT) at the primary centre—including noncontrast CT, CT perfusion, and CT angiography—may enhance reperfusion therapy decision‐making. We developed a network with five spoke primary stroke sites and assessed safety, feasibility, and influence of mCT in rural hospitals on decision‐making for thrombolysis. Methods: Consecutive patients assessed via telemedicine from April 2013 to June 2018. Clinical outcomes were measured, and decision‐making compared using theoretical models for reperfusion therapy applied without mCT guidance. Symptomatic intracranial hemorrhage (sICH) was assessed according to Safe Implementation of Treatments in Stroke Thrombolysis Registry criteria. Results: A total of 334 patients were assessed, 240 received mCT, 58 were thrombolysed (24.2%). The mean age of thrombolysed patients was 70 years, median baseline National Institutes of Health Stroke Scale was 10 (IQR 7‐18) and 23 (39.7%) had a large vessel occlusion. 1.7% had sICH and 3.5% parenchymal hematoma. Three months poststroke, 55% were independent, compared with 70% in the non‐thrombolysed group. Conclusion: Implementation of CTP in rural centers was feasible and led to high thrombolysis rates with low rates of sICH.